Penerapan Kompres Daun Kol terhadap Pembengkakan Payudara Pada Ibu Post Partum di Kecamatan Karangdowo - Siti Erlinawati; Mulyaningsih Mulyaningsih (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Breast swelling in post partum mothers if not immediately resolved will cause mastitis and breast abscess. There are 32.6% of infants in Jawa Tengah who have not met exclusive breastfeeding with the main factor due to breast swelling. One of the non-pharmacological therapies used is cabbage leaf compress. This study describes the comparison of the development of breast swelling scale before and after the application of cabbage leaf compress. This research uses a case study of 2 respondents carried out for 3 consecutive days in the morning and evening with a duration of 15-20 minutes. the application of cabbage leaf compresses on both respondents obtained comparative results, namely in Mrs. A breast swelling scale 1 and in Mrs. T scale 2. The results of the study can be concluded that there is an effect of cabbage leaf compresses on the scale of breast swelling in both respondents.